Analisis Optimalisasi Produksi Dengan Linear Programming Melalui Metode Simpleks (Studi Kasus UMKM Aqisa Rumah Rosella Surabaya) - Diva Suroso, Jastino Saddam; Nugroho, Prasetyo (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
The simplex method is a method used to solve linear programming problems with repeated (repeated) calculations done many times to reach an optimal solution.  To solve linear programming problems, it is necessary to determine the constraints and inequalities contained in the linear program.  The simplex method can solve linear programming problems involving many inequalities and many variables.  This study aims to optimize the production of rosella flower tea drinks and rosella flower syrup at UMKM Aqisa Rumah Rosella Surabaya.  This study is a literature study, namely a literature study by examining books, journals and reports that are relevant to the field under study.  The steps for optimizing production results include: (1) observation, (2) data collection, (3) mathematical modeling, (4) optimizing production results using the simplex method, (5) optimizing production results using POM-QM.  The results of simplex linear program calculations using the POM-QM application, in order to get maximum profit, UMKM Aqisa Rumah Rosella needs to increase production of rosella tea drinks to 35 bottles per day and for rosella syrup it is necessary to reduce production to 5 bottles per day.  With a total profit of IDR 142,500.  Profits earned increased by 5%